2009
DOI: 10.1051/dst/2009008
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding capacity of organic and inorganic ortho- and polyphosphates

Abstract: -The aim of this research was to determine the calcium-binding capacity of inorganic and organic ortho-and polyphosphates. This calcium-binding capacity can be used to influence the stability of, for example, casein micelles in dairy systems. Four phosphates were selected: disodium uridine monophosphate (Na 2 UMP, organic orthophosphate), disodium hydrogen phosphate (Na 2 HPO 4 , inorganic orthophosphate), sodium phytate (SP, organic polyphosphate), and sodium hexametaphosphate (SHMP, inorganic polyphosphate).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…1). In a previous study, a strong decrease in pH for SHMP in a calcium chloride solution upon heating was observed (De Kort et al, 2009). SHMP hydrolyzes into sodium trimetaphosphate and sodium orthophosphate in acidic conditions (Van Wazer, 1958) and this hydrolysis probably occurred to some extent in the MCI solutions during heating as well.…”
Section: Effect Of Sodium Hexametaphosphatementioning
confidence: 85%
See 3 more Smart Citations
“…1). In a previous study, a strong decrease in pH for SHMP in a calcium chloride solution upon heating was observed (De Kort et al, 2009). SHMP hydrolyzes into sodium trimetaphosphate and sodium orthophosphate in acidic conditions (Van Wazer, 1958) and this hydrolysis probably occurred to some extent in the MCI solutions during heating as well.…”
Section: Effect Of Sodium Hexametaphosphatementioning
confidence: 85%
“…As these chelators carry different amounts of negative charges, this results in different calciumbinding capacities (De Kort, Minor, Snoeren, Van Hooijdonk, & Van der Linden, 2009). The concentration ranges of the calcium chelators were based on milliequivalents to obtain an equal amount of charges in the samples.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…3b), indicating the release of protons. De Kort, Minor, Snoeren, Van Hooijdonk, and Van Der Linden (2009) and Vujicic, Batra, and Deman (1967) indicated that the cause of the pH drop is due to the replacement of hydrogen by calcium from the polyphosphates. However, according to De Kort et al (2009), SHMP has been recognised as a cyclic compound with six metaphosphate monomers (NaPO 3 ) 6 , as shown in Fig.…”
Section: Effect Of Shmpmentioning
confidence: 99%